Estimation of the algal-available phosphorus pool in sediments of a large, shallow eutrophic lake (Taihu, China) using profiled SMT fractional analysis - Zhu, Mengyuan; Zhu, Guangwei; Li, Wei; Zhang, Yunlin; Zhao, Linlin; Gu, Zhao (Environmental pollution (1987), 2013)
Because large, shallow lakes are heavily influenced by wind–wave disturbance, it is difficult to estimate internal phosphorus load using traditional methods. To estimate the potential contribution of phosphorus from sediment to overlying water in eutrophic Lake Taihu, phosphorus fractions of surface and deep layer sediments were quantified and analyzed for algal bloom potential using a Standard Measurements and Testing (SMT) sequential extraction method and incubation experiments. Phosphorus bound to Fe, Al and Mn oxides and hydroxides (Fe–P) and organic phosphorus (OP) were to be found bioactive. The difference in Fe–P and OP contents between surface and deep layers equates to the sediment pool of potentially algal-available phosphorus. This pool was estimated at 5168 tons for the entire lake and was closely related to pollution input and algal blooms. Profiled SMT fractionation analysis is thus a potentially useful tool for estimating internal phosphorus loading in large, shallow lakes. ► We used profiled sediment P activity by SMT fractionation to evaluate the P release potential in large and shallow lakes. ► We built the relationship between sediment SMT fractionations of P and the P release by algal bloom degradation process. ► We discussed the supporting mechanism of sediment P release to Microcystis algal bloom in a large and shallow lake. ► We discussed the nutrient control strategy of algal bloom in shallow lakes in highly human activities disturbance catchment. Profiled SMT fractional analysis of internal phosphorus pool in large, shallow lake.